Egocentric physics: Just about Mie. (3rd November 2017) - Stout, Brian; McPhedran, Ross
Abstract: We show that the physics of anapole excitations can accurately be described in terms of a truncated resonant state expansion formulation of standard Mie theory as an alternative to the recently advocated "toroidal" current description. In the purely Mie framework, the anapole behavior arises as a result of a Fano-type interference effect between different resonant states with complex wave numbers, provided that non-singular phase factors associated with causality are properly taken into account.